2014
DOI: 10.1016/j.nlm.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Encoding and reinstatement of threat: Recognition potentials

Abstract: On a recognition test, stimuli originally encoded in the context of shock threat show an enhanced late parietal positivity during later recognition compared to stimuli encoded during safety, particularly for emotionally arousing stimuli. The present study investigated whether this ERP old/new effect is further influenced when a threat context is reinstated during the recognition test. ERPs were measured in a yes-no recognition test for words rated high or low in emotional arousal that were encoded and recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…More specifically, subsequent recollection was enhanced for stimulus words encoded under a condition in which a painful electric shock was anticipated (signaled by the color of a stimulus – i.e., within-object binding), compared to those encoded under a safety (no-shock) condition ( Figure 5B ). Interestingly, the observed context effects on memory were most reliable for emotional events ( Weymar et al, 2013 , 2014 ), which fits with the ABC theory ( Mather and Sutherland, 2011 ) positing that arousal (e.g., threat of shock) during encoding may facilitate subsequent recollection of prioritized information (e.g., emotionally salient words). These studies also show that a context bound to an event is not restricted to the actual experience but also to its mere anticipation ( Maren et al, 2013 ).…”
Section: Emerging Directions In Emotional Episodic Memorysupporting
confidence: 78%
See 1 more Smart Citation
“…More specifically, subsequent recollection was enhanced for stimulus words encoded under a condition in which a painful electric shock was anticipated (signaled by the color of a stimulus – i.e., within-object binding), compared to those encoded under a safety (no-shock) condition ( Figure 5B ). Interestingly, the observed context effects on memory were most reliable for emotional events ( Weymar et al, 2013 , 2014 ), which fits with the ABC theory ( Mather and Sutherland, 2011 ) positing that arousal (e.g., threat of shock) during encoding may facilitate subsequent recollection of prioritized information (e.g., emotionally salient words). These studies also show that a context bound to an event is not restricted to the actual experience but also to its mere anticipation ( Maren et al, 2013 ).…”
Section: Emerging Directions In Emotional Episodic Memorysupporting
confidence: 78%
“…The observed parietal Old/New effect (>400 ms following the stimulus onset) has been associated with recollection-based remembering ( Rugg and Curran, 2007 ; Weymar and Hamm, 2013 ), thus suggesting that objects from emotional contexts were better recollected than those from neutral contexts. A similar ERP signature of memory retrieval has been identified for stimuli encoded under threat of shock ( Weymar et al, 2013 , 2014 ). More specifically, subsequent recollection was enhanced for stimulus words encoded under a condition in which a painful electric shock was anticipated (signaled by the color of a stimulus – i.e., within-object binding), compared to those encoded under a safety (no-shock) condition ( Figure 5B ).…”
Section: Emerging Directions In Emotional Episodic Memorysupporting
confidence: 58%
“…Similar to classically conditioned fear (Hamm et al, 1993;Lipp et al, 1994), verbally instructed threat signals primed defensive response programs, as indicated by potentiated startle reflex, enhanced electrodermal activity, and self-report data (Bradley et al, 2005;Bublatzky et al, 2013;Grillon et al, 1991;Melzig, Weike, Hamm, & Thayer, 2009). Taken together with studies that indicate facilitated stimulus processing and memory function under threat of shock, these findings demonstrate that the instructed threat paradigm is a reliable tool to provoke aversive anticipation even without the actual experience of CS-UCS associations (Bublatzky et al, 2010;Bublatzky & Schupp, 2012;Cornwell et al, 2007;Weymar, Bradley, Hamm, & Lang, 2013, 2014.…”
Section: Discussionmentioning
confidence: 83%
“…As for the encoding data, previous research on recognition memory also found a memory advantage for pleasant words (Herbert et al, 2008 ). However, it should be noted that arousal-specific effects or even unpleasant enhancing effects have also been reported (Kensinger and Corkin, 2003 ; Weymar and Hamm, 2013 ; Weymar et al, 2014 ). The inconsistent effects of arousal and valence on recognition memory across studies may, however, be a result of differences in arousal and valence levels of the stimuli used in experiments and may also be related to differences in lexico-semantic variables, such as the frequency, concreteness, imageability, age of acquisition, and familiarity of words (Scott et al, 2009 ; Kousta et al, 2011 ), which also likely lead to differences in word processing studies.…”
Section: Discussionmentioning
confidence: 97%